A method to approximate first passage times distributions in direct time Markov processes - Ferreira, Manuel Alberto M. (2013)
A numerical method to approximate first passage times distributions in direct Markov processes will be presented. It is useful to compute sojourn times in queue systems, namely in Jackson queuing networks. Using this method (Kiessler et al., 1988) achieved to clear a problem that arises in the Jackson three node acyclic networks sojourn times.